2017
DOI: 10.5219/690
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the pressing process during oil extraction from grape seeds

Abstract: This study evaluated the physical properties and oil extraction from grape seeds from three white (Welschriesling, Green Veltliner, Hibernal) and two red (Zweigelt and Saint Laurent) must varieties of grapevine by cold screw pressing as the appropriate extraction process. Pressing was carried out by a screw press UNO FM 3F by Farmet Company, Czech Republic. The pressing device consists of a matrix, 220 mm screw, head, heating mantle, nozzle holder, and a nozzle of 10 mm in diameter. The minimal and maximal scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Burg [16] aimed evaluation of grape seed oil extraction process and 3 white (Welschriesling, Green Veltliner, Hibernal) and 2 red (Zweigelt ve Saint Laurent) grape seeds used for oil production. All seeds moisture and oil contents, 1000 grain weight, density were determined.…”
Section: Parameters That Affect Product Yield In Cold Press Extractionmentioning
confidence: 99%
“…Burg [16] aimed evaluation of grape seed oil extraction process and 3 white (Welschriesling, Green Veltliner, Hibernal) and 2 red (Zweigelt ve Saint Laurent) grape seeds used for oil production. All seeds moisture and oil contents, 1000 grain weight, density were determined.…”
Section: Parameters That Affect Product Yield In Cold Press Extractionmentioning
confidence: 99%
“…On the other hand, triesters can hydrolyze and produce glycerides and free fatty acids, and non-saturated chains can react with oxygen to produce oxidative products responsible for lipids deterioration. These two phenomena are the cause of two major forms of changes in food fats, i.e., acidification and oxidation (Burg et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The highest oil yield was obtained the inlet temperature of 80°C, the feed flow rate of 0.4 kg/h, and screw rotation rate of 20 rpm, while the lowest oil yield was found in the highest inlet temperature. There are some other studies, which investigated the critical parameters affecting oil amount in cold pressing extraction such as characteristics of the raw material (moisture content, oil content, and type of raw material) (Burg et al., 2017; Rombaut et al., 2015), feed rate (Teh, 2016), temperature (Rabadán et al., 2018), cold rotation speeds (Teh, 2016), and, pre‐treatment (Pare et al., 2014), etc. Since the effects of parameters used in this study on the oil extraction were found significant in the previous studies and the effects of these parameters on tomato seed oil extraction by the cold‐pressing method have not been searched before, these parameters were chosen for the optimization.…”
Section: Resultsmentioning
confidence: 99%
“…Burg et al. (2017) were found the significant effect of screw rotation rate on the oil extraction from grape seed (Burg et al., 2017). Rabadan et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation